ASUHAN KEBIDANAN IBU HAMIL, BERSALIN, NIFAS, DAN BAYI BARU LAHIR PADA NY.H DI BPM SEMI NURYATI Amd.Keb KECAMATAN NGOMBOL - Shaella Kusuma P; Restu Pangestuti (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2022)
To improve maternal and neonatal health and health services to reduce maternal and infant mortality, comprehensive midwifery care was carried out for Ny. Hermawati from 41 weeks of pregnancy, maternity, postpartum, newborn and family planning at BPM. Semi Nuryati Amd.Keb. The purpose of the case study is to provide comprehensive midwifery care according to Varney's 7 steps to Ny. H at BPM. Semi Nuryati Amd. Keb, Ngombol, Purworejo. The research method used is descriptive observational. In the case study, Mrs. Hermawati starting from pregnancy, childbirth, postpartum, BBL and physiological family planning was carried out using data collection techniques, namely interviews, observation, examination and documentation. The results of the case report and discussion are the authors carry out comprehensive midwifery care for Ny. Hermawati from pregnancy got normal results, maternity care obtained normal delivery mothers and babies born spontaneously normally, from BBL care obtained normal baby conditions, postpartum care obtained normal results and mother's family planning care using 3-month injections. In this case study, a gap between practice and theory was found, namely in umbilical cord care.